Drugs Compromising Male Sexual Health - Krause, Walter K.H. (Springer, 2017)
This concise drug guide lists 500 substances, such as pharmaceutical drugs, lifestyle drugs, and environmental toxicants, which show documented untoward effects on the male sexual organs and their functions. All substances are listed in user-friendly alphabetical order with a uniform structure throughout the book. Each listing includes evidence-based information with up-to-date references and all studies mentioned are evaluated and categorized according to study and sample types. This unique compendium provides more detailed information on each drug than any other standard pharmacology title.